Cocaine and other psychostimulant consumption: their relationship with the childhood hyperactivity syndrome - Ros Soler, A.; Valoria Martínez, A.; Nieto Munuera, J. (Actas Españolas de Psiquiatría, 2004)
Introduction. We want to know the attention deficit hyperactivity disorder (ADHD) among those subjects who require treatment due to cocaine and other psychostimulant drugs consumption. No previous Spanish studies have been found. Methods. Two groups of male subjects were established out of a total of 109 subjects. Their ages ranged from 16 to 40 years. The groups were «experimental» (patients under treatment) and «control», who underwent a urine analysis for toxic agents. An interview elaborated for this and the E mode SCID-I were used. A total of 21 % of the cocaine consumers had a comorbid history of ADHD in childhood versus 3 % of the control group. Conclusions. The data found overlap with the United States studies. ADHD appears as a new risk factor for the posterior development of cocaine abuse disorder, adding a cocaine addict patient subtype that deserves special diagnostic criteria as well as more complete treatment alternatives for these dual diagnosed patients.